Perancangan Sistem Informasi Booking Online Aplikasi Salon SPA Beauty Devi Berbasis Mobile - Devi, Sri; badra, Aditya Pratama badra; Hidayati, Awanis Hidayati (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2025)
Salon and spa services are increasingly in demand, especially among women, as awareness of hygiene, appearance, and the need for relaxation grows. However, many businesses in this sector have yet to adopt digital systems, particularly for reservations and service management. One such example is Salon & Spa Beauty Devi, located in Pontianak, which still relies on manual records and bookings. This results in various operational issues, such as scheduling conflicts, data loss, and slow service processes. Previous studies have shown that mobile-based reservation systems can improve service efficiency and enhance customer experience. Therefore, this study aims to design an online reservation information system based on a mobile application for Salon & Spa Beauty Devi. The implementation of this system is expected to improve service management, streamline operations, and address the challenges of digitalization in the modern era